Project MediWeB, Assessment of the impact of Mediterranean diet and other lifestyle factors on well-being - Report 2019 and 2020 - Pinto, Paula (2020)
During the first two years of the MeDiWeB research consortium, the following tasks were completed: 1) Design of the validation protocol and the online MeDiWeB questionnaire, and submission to the Ethic Commission of each participating institution. 2) After approval by the Ethic Commission, each institution performed the validation of the Mediterranean diet assessment instrument (MEDAS): recruitment of voluntaries; collection of three-day food diaries and two food frequency questionnaires; standardization of data according to an excel template. 3) Dissemination of the on-line MeDiWeB questionnaire; data collection and standardization according to an excel template. 4) Analysis of data from validation and publication of one paper. 5) Partial analysis of data from MeDiWeB Questionnaire and publication of one paper.